Effectiveness of the KC@H programme compared with clinic-based rehabilitation in patients recovering from ACL reconstruction - Alegrete, Joana (2024)
Funding Information: Funding This trial is funded by FCT/MCTES as part of the Multiannual Financing of R&D Units 2020–2023. It is a collaboration between FCT and the R&D Unit CHRC—Comprehensive Health Research Centre (NMS|FCMUNL), (UIDP/04923/2020), with Reference UIDP/04923/2020| CHRC| 2021. This work is funded by national funds through the Foundation for Science and Technology under the project UIDP/04923/2020. Funding Information: This trial is funded by FCT/MCTES as part of the Multiannual Financing of R&D Units 2020–2023. It is a collaboration between FCT and the R&D Unit CHRC—Comprehensive Health Research Centre (NMS|FCMUNL), (UIDP/04923/2020), with Reference UIDP/04923/2020| CHRC| 2021. This work is funded by national funds through the Foundation for Science and Technology under the project UIDP/04923/2020. Publisher Copyright: © 2024 BMJ Publishing Group. All rights reserved.